Tanggap Tiga Varietas Kedelai Sebagai Tanaman Sela di Perkebunan Karet TBM 1 Terhadap Pemberian Rhizobium - Imam, muhammad; Mawarni, Lisa; Siregar, Luthfi A. M. (Jurnal Agroekoteknologi, 2016)
Muhammad Imam. Response of Three Soybean Varieties as Intercrop in First Immature Periode of Rubber Tree to Rhizobium Application, supervised by Lisa Mawarni, Luthfi Aziz Mahmud Siregar and Radite Tistama The aim of this research was to determinate the growth aMuhammad Imam. Response of Three Soybean Varieties as Intercrop in First Immature Periode of Rubber Tree to Rhizobium Application, supervised by Lisa Mawarni, Luthfi Aziz Mahmud Siregar and Radite Tistama The aim of this research was to determinate the growth and production effect of three soybean varieties (Glycine max (L) Merril) on the rubber plant inter row in first immature periode of rubber (Hevea brasiliensis Muell) plantation. This research was conducted at the Sunge Putih Research Centre with altitude ± 80 m above sea level, in August until November 2014. The research was using a block randomized design with two factors and three replications. The first factor was variety IPB 1, Wilis, Anjasmoro and the second factor was Rhizobium (Density 109g or ml/plant) then without Rhizobium. The results showed that the differences in varieties had significantly effect on plant height of age 2-5 (week after plant), age 2-3 (week after plant), summarize of leaf area, mean number of productive branches, root fresh weight, root dry weight, and weight of 100 seeds per plot. Inoculation rhizobium significantly effect on summarize of leaf aera and mean number of productive branches. Interaction of the two factors had not significantly effect to all parameters were observed.   Keywords : Soybean varieties, Rhizobium, and inter rownd production effect of three soybean varieties (Glycine max (L) Merril) on the rubber plant inter row in first immature periode of rubber (Hevea brasiliensis Muell) plantation. This research was conducted at the Sunge Putih Research Centre with altitude ± 80 m above sea level, in August until November 2014. The research was using a block randomized design with two factors and three replications. The first factor was variety IPB 1, Wilis, Anjasmoro and the second factor was Rhizobium (Density 109g or ml/plant) then without Rhizobium. The results showed that the differences in varieties had significantly effect on plant height of age 2-5 (week after plant), age 2-3 (week after plant), summarize of leaf area, mean number of productive branches, root fresh weight, root dry weight, and weight of 100 seeds per plot. Inoculation rhizobium significantly effect on summarize of leaf aera and mean number of productive branches. Interaction of the two factors had not significantly effect to all parameters were observed.   Keywords : Soybean varieties, Rhizobium, and inter row